Economic Systems - Duhaime, Gérard; Lemelin, André; Didyk, Vladimir; Goldsmith, Oliver; Winther, Gorm; Caron, Andrée; Bernard, Nick; Godmaire, Anne (Arctic Council, 2024)
The formal economy of the Arctic is mainly based on large-scale exploitation of natural resources (e.g. mineral, oil and gas, and fish), most of which are exported. The service sector is well developed in many parts of the Arctic, whereas manufacturing plays a relatively minor role. Public services are often supported by transfer payments from central governments but overall, more money is flowing out of the Arctic than into the region. The large-scale exploitation of Arctic resources is important to the national economies of several Arctic countries, as well as in the global economy. This is especially true for the Russian Arctic. The size and structure of the economy differ between and within countries. The gaps between wealthy and poor regions appear everywhere but are most extreme in Russia and North America. The Arctic is likely to continue to play a role as a reservoir of resources for the rest of the world. New trends are privatization of resources and new forms of economic partnerships. 0